ANALYSIS OF ECONOMIC AND LABOR GROWTH ON THE REDUCTION OF THE NUMBER OF POOR POPULATION IN JAMBI - Nengsih, Titin Agustin; Yulianti, Risty; Kirana, Sashi Syalwa; Almansyah, Almansyah; Majid, M.Nazori; Usdeldi, Usdeldi; Rahma, Sri; Mutia, Agustina (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study examines the impact of labour force expansion and economic growth on the decline in the impoverished population in Jambi using data from 2019 to 2021. This research employed a quantitative methodology, meaning that numerical data were analysed using multiple linear regression statistics. To analyse the effects of labour force participation, economic growth, and the poor population variable, secondary data from the BPS (Central Statistics Agency) data was did. The findings of this research indicate that the labour force variable has a considerable impact on the impoverished population, however the economic growth variable has no positive or significant influence on this population.